﻿Entyposis frici (Coleoptera, Scarabaeidae, Melolonthinae), a new species from Somaliland - Aleš Bezděk; Richard Sehnal; Hassan S. A. Elmi; David Sommer; David Král (ZooKeys, 2023)
Entyposis frici Bezděk & Sehnal, sp. nov., from Somaliland is described and relevant diagnostic characters are illustrated. The new species is compared with the morphologically closely similar Entyposis Kolbe, 1894 species. An updated checklist and an identification key to northeastern African Entyposis species are provided.